Maulid and shalawat in Popular Culture Perspective (study of Jami'iyah Ahbabul Musthofa Yogyakarta) - Rifqi Fairuz (Faculty of Adab and Cultural Studies Sunan Kalijaga Islamic State University, 2013)
st,1/oen, .01